Ammonium and non-sea salt sulfate in the EPICA ice cores as indicator of biological activity in the Southern Ocean - Kaufmann, Patrik; Fundel, Felix; Fischer, Hubertus; Bigler, Matthias; Ruth, Urs; Udisti, Roberto; Hansson, Margareta; de Angelis, Martine; Barbante, Carlo; Wolff, Eric W.; Hutterli, Manuel; Wagenbach, Dietmar (Quaternary science reviews, 2010)
Sulfate (SO42−) and ammonium (NH4+) flux records over the last 150,000years from both Antarctic EPICA ice cores (European Project for Ice Coring in Antarctica) are presented. The ice core record from Dome C is influenced by the Indian sector of the Southern Ocean (SO), whereas Dronning Maud Land is facing the Atlantic sector. Generally, they reflect the past atmospheric aerosol load and, thus, potentially reveal the fingerprint of marine biogenic sources from the SO. The most important feature of both, the nssSO42− as well as NH4+ flux records, is the absence of any significant glacial cycles, in contrary to the distinct transitions for mineral dust and sea salt aerosol over the last 150,000years. This finding challenges the iron fertilization hypothesis on long time scales, as the significant changes in dust, e.g. from the last glacial maximum toward the Holocene have neither an impact on nssSO42− nor on NH4+ fluxes found in interior Antarctica. The inter-site correlation of both species is weak, r2=0.42 for the nssSO42− flux and r2=0.12 for the NH4+ flux respectively, emphasizing the local source characteristics of biogenic aerosol from the SO. Millennial variability in NH4+ and nssSO42− is within the uncertainty of our flux estimates. Correlation with mineral dust and sea ice derived sodium shows only a very weak influence of dust deposition on those insignificant changes in nssSO42− flux for the Atlantic sector of the Southern Ocean, but also small transport changes or terrigeneous sulfate contributions may contribute to those variations at EDML.